Implementation Of Halal Supply Chain Management in The Supply Of Chicken Meat At Market Raya Padang - Wahyu Kurniawan; Hendri Andi Mesta (Devitara Innovations, 2024)
In Padang there are many traditional markets, but not all markets have permission to slaughter poultry in the market because there are still many markets that do not meet the requirements. In the traditional markets of Padang city that meet the terms and conditions for slaughtering poultry, one of them is the Padang fair market. Apart from that market, there are also those who are not allowed to slaughter poultry in the market. However, currently there are still many cuts being carried out in traditional markets in Padang, including Mr Taufik's cuts in the Padang Raya market. Based on the results of field observations that I carry out with workers every day, these cuts can be prepared. chickens that are ready to sell are 70 kw. So, because of the differences, researchers want to understand the supply chain in depth, the differences between cuts that are permitted and cuts that are not permitted. The author's consideration for choosing a qualitative approach is because the qualitative approach is carried out in natural conditions, or focuses directly on the data source so that in-depth information and more valid data will be obtained in accordance with the research background and field conditions. Based on this research, the population is not greater than 100 respondents, so the author took 100% of the population at Pasar Raya Padang, namely 12 respondents. The implementation of halal supply chains for chicken traders at Pasar Raya Padang has shown a strong commitment to fulfilling halal standards in the supply chain. These chicken traders have taken important steps in ensuring the halalness of their products, starting from selecting trusted suppliers to strict quality control practices. Chicken traders have paid attention to various important aspects in the halal supply chain, including selecting trusted suppliers, appropriate slaughtering processes with Islamic principles, separation of halal and non-halal products, as well as maintenance of cleanliness and sanitation at every stage of the production, storage, transportation and sales processes. challenges faced by chicken traders, such as high costs to obtain halal certification, lack of attention on the halalness of chicken feed, and the need for updates in halal supply chain management practices. Traders need to pay more attention to the halalness of the chicken feed ingredients used to ensure that the entire production process meets halal standards. Chicken traders need to maintain the quality of the chicken meat they sell and provide understanding to consumers to pay attention to the quality of the chicken meat they buy. Traders should consider obtaining halal certification as a step to increase consumer confidence and the sustainability of their business. Traders can take additional steps to increase transparency and accountability in the halal supply chain, such as by increasing the use of technology and information systems.